Synthesis and Neuroprotective Action of Optically Pure Neoechinulin A and Its Analogs - Toshiaki Aoki; Kensuke Ohnishi; Masaaki Kimoto; Satoshi Fujieda; Kouji Kuramochi; Toshifumi Takeuchi; Atsuo Nakazaki; Nobuo Watanabe; Fumio Sugawara; Takao Arai; Susumu Kobayashi (MDPI AG, 2010)
We developed an efficient, stereoselective synthetic method for the diketopiperazine moiety of neoechinulin A and its derivatives. The intramolecular cyclization at 80 ºC proceeded with minimal racemization of the stereogenic center at C-12 on neoechinulin A, even though the cyclization at 110 ºC caused partial racemization. In contrast with these results, the cyclization on diketopiperazine of 8,9-dihydroneoechinulin A derivatives did not cause epimerization of the stereogenic centers, even at 110 °C. We examined the structure-activity relationships for the cytoprotective activity against cytotoxicity induced by 3-morpholinosydnonimine (SIN-1) in nerve growth factor (NGF)-differentiated PC12 cells. The C-8/C-9 double bond, but not the stereogenic center derived from alanine, was found to play a key role in the cytoprotective activity.